Trauma and Public Mental Health: A Focused Review - Kleber, Rolf J. (Frontiers in Psychiatry, 2019)
Psychological trauma has developed into a very common concept in the scientific community, in mental health care, as well as in popular language and mass media. The purpose of this article is to show the relevance of the discipline of traumatic stress studies to the field of public mental health by examining central concepts and findings concerning trauma and its aftermath and examining implications for public mental health. Attention is paid to the diagnosis of posttraumatic stress disorder (PTSD) and the construct of resilience as well as to specific areas of public mental health activities. A public mental health perspective will help to develop preventive approaches to trauma and extend the impact of various forms of interventions. It will also make clear that trauma care will have to consider the community and the society at large.